Genes of Salmonella enterica Serovar Enteritidis Involved in Biofilm Formation - Seulgi Lee; Jinru Chen (Applied Microbiology, 2024)
Although biofilms contribute to bacterial tolerance to desiccation and survival in low-moisture foods, the molecular mechanisms underlying biofilm formation have not been fully understood. This study created a mutant library from Salmonella Enteritidis using mini-Tn10 transposon mutagenesis. The biofilm-forming potential of acquired mutants was assessed before the genomic DNA of the mutants that formed significantly (p ≤ 0.05) less biofilm mass than their wildtype parent strain was extracted for deep DNA sequencing. The gene of each mutant interrupted by mini-Tn10 insertion was identified by aligning obtained sequencing data with the reference Genbank sequences using a BLAST search. Sixty-four mutant colonies were selected, and five mutants that formed the least amount of biofilm mass compared to the wildtype parent strain were selected for sequencing analysis. The results of the BLAST search revealed that the gene interrupted by mini-Tn10 in each mutant is responsible for the biosynthesis of aldehyde dehydrogenase (EutE), cysteine desulfurase (SufS or SufE), a transporter protein, porin OmpL, and a ribbon–helix–helix protein from the CopG family, respectively. Knock-off mutant construction is a possible approach to verify the potential of the identified genes to serve as targets of antimicrobial intervention to control Salmonella colonization on low-moisture foods and in their production environment.